Exploration of Salt Farmers’ E-Marketing Strategy: A Lesson from Madura Island, Indonesia - AS, Fathor; Fatmariyah, Fatimatul (International Review of Management and Marketing, 2023)
This study aims to explore various e-marketing strategies that salt farmers might use. The qualitative-descriptive method was chosen as the method used in this research. Researchers collected data by observing, conducting interviews, and documenting our studies. The method of analysis is known as descriptive-qualitative analysis. The findings indicated that salt farmers’ knowledge of the various forms of e-marketing media was satisfactory. However, their expertise consisted just of knowledge, and they needed to learn how to make the most of the existing media to exploit it as a promotional tool. Although salt farmers are already familiar with many different media that can use as marketing media, the most excellent e-marketing technique for business uses only Facebook networking or social media marketing strategy.